Juridical Analysis of Car Rental Agreements (Study at PT. Persada Solo) - Dhimas Ardiansyah; Andria Luhur Prakoso (Universitas Muhammadiyah Surakarta, 2023)
Relations between humans in the era of globalization are very urgent, especially in activities to fulfill their needs. Humans, in order to fulfill life's affairs, are obliged to maintain social activities between humans. This form of interaction can also take the form of legal action. Legal relationships are relationships regulated by law. The relationships regulated in this law are the relationships between the rights and obligations of state residents, between individuals and citizens, and with other people in social life.Agreements can be made by anyone who has an interest in making an agreement, and each party has the authority to make an agreement, unless the law determines that they do not. Failure to speak is defined in article 1330 of the Civil Code.The writing model used in this article is normative legal review, namely research carried out by examining various legal provisions of various forms such as laws, regulations and literature containing theoretical principles which are then linked to the discussion of this journal. The strategy used is a statutory approach and then a conceptual approach. In the PT Persada Solo agreement, it is a valid agreement but there is a party who must compensate for losses in this incident, someone must replace the damage to the car. And you can choose which route to take, whether through court or non-litigation. The agreement with PT Persada Solo is regulated by several rules in Indonesia, for examplearticle 1313 of the Civil Code,Government Regulation no. 41 of 1993 concerning Road Transport as wellArticle 1548 of the Civil Code essentially means renting. In essence, the legal cause of legal action is that sanctions are imposed on those who are found guilty or have violated the agreement.